Fenomena Penutupan Jalan Umum Untuk Acara Kedukaan Di Wilayah Kampung Kei Kota Jayapura (The phenomenon of Closing Public Roads for Grief Events in Kei Village Area Jayapura City) - Marwan Sileuw; Siti Komariah Tiflen; Muhamad Yusuf; Muhammad Rusdi Rasyid (Institut Agama Islam Negeri (IAIN) Manado, 2022)
The road closures were carried out by residents of Kei Abepura Village, Yobe Village, and Abepura District when there was grief, as well as during worship for mourning activities of residents living around Grilyawan Street of Abepura Kei Village, so that the road for vehicles from the direction of Keerom, Abe Pantai and Koya was diverted turn to the direction to the Mental Hospital or through the small alleys in the upper complex of the Kei Abepura village to get to the Abepura circle area, for the opposite direction, namely from the Abepura circle, they have to pass Youtefa to get out to Tanah Hitam, Abe Pantai, Koya, and Keroom. This research purposes to find out the road closure model, the general public’s response, and the occurrence of the road closures carried out by the residents of Kei Village when there is grief in the residents of Kei Village, Abepura District, Jayapura City. This study uses a qualitative research method with the paradigm of social phenomenology. The results show that road closures for mourning activities are an alternative that is taken due to the absence of residents' yards which leads to various perceptions from the general public about the closure of provincial roads for personal activities. It takes clear rules issued by the local government regarding the use of public facilities for personal or group interests. It also requires public awareness about prioritizing the public interest over personal or group interests.